Meromorphic functions with deficiencies generating unique range sets - Abhijit Banerjee; Sujoy Majumder (Հայաստանի ԳԱԱ)
With the help of weighted sharing of sets we deal with the problem of unique range set for meromorphic functions with deficient values and obtain a result which improves, generalizes and extends some previous results. We provide two examples to show that the condition in one of results is the best possible.
Keywords: Mathematics; Science